Perkembangan Muhammadiyah di Kabupaten Aceh Tenggara, 1955-2022 - Anggriani, Mirna; Sumanti, Solihah Titin; Syam, Abdi Mubarak (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
Established in 1937, Muhammadiyah made its debut in Southeast Aceh through Minangkabau migrants, propagating its teachings and organization. Despite initial challenges, including misconceptions labeling Muhammadiyah as Wahabi or Salafi, it emerged as a Quran and Hadith-based movement. Utilizing historical research methods, this study explores Muhammadiyah's impact on Southeast Aceh, revealing rapid acceptance among the Alas people due to their existing religious understanding. Muhammadiyah significantly influenced the region, targeting social, educational, and religious spheres for renewal. Its presence led to the establishment of educational institutions and social development, resonating deeply with the community's needs. Muhammadiyah's role in Southeast Aceh exemplifies its broader mission to enrich Islamic practices and community welfare, underscoring its profound influence in the region's religious and social landscape. Through its multifaceted initiatives, Muhammadiyah continues to shape the socio-religious fabric of Southeast Aceh, embodying a dynamic force for positive change in the community.